A multidimensional in-depth analysis of postoperative pain after PLIF in patients with degenerative lumbar spine disease - Tang, Ting; Sun, Xiao; Sun, Haifu; Li, Yonggang; Wang, Yimeng; Chen, Dan (Frontiers in Medicine, 2025)
PurposeTo comprehensively investigate multifactorial influences on postoperative pain in patients with degenerative lumbar spine disease undergoing posterior lumbar interbody fusion (PLIF), thereby guiding targeted rehabilitation.Patients and methodsWe reviewed 316 patients (age >40) who underwent PLIF from January 2022 to May 2024. Based on postoperative Numeric Rating Scale (NRS) scores and pain duration, they were divided into a non-pain group (210 cases) and a pain group (106 cases). We assessed paraspinal muscle indices (PMI, MMI), Self-Rating Anxiety Scale (SAS), postoperative exercise duration, surgical segments, drainage removal time, and mannitol usage. Univariate and multivariate logistic regression analyses were conducted.ResultsNo significant differences were found in age, BMI, education, surgical duration, drainage time, disease duration, time to first ambulation, or mannitol usage (P > 0.05). However, gender, SAS scores, surgical segments, drainage volume at removal, PMI, MMI, average standing time in the first 2 weeks, and duration of straight-leg raise exercises differed significantly (P < 0.05). Multivariate analysis identified surgical segment (P = 0.008), drainage volume at removal (P = 0.008), MMI (P < 0.001), average standing time (P = 0.010), and straight-leg raise exercise duration (P = 0.012) as independent risk factors.ConclusionParaspinal muscle health and early postoperative exercise are crucial factors influencing PLIF-related postoperative pain. Tailored rehabilitation, enhanced muscle function, and optimized early exercise may reduce postoperative pain and improve outcomes.